Rare pontine metastasis operated via endoscopic transsphenoidal transclival approach, a case report and brief review of literature - Amr El Mohamad (Elsevier, 2022)
Background: Brain metastasis from endometrial adenocarcinoma is uncommon, and to the brain stem particularly are quite rare. Different therapeutic modalities for metastatic endometrial cancer to the brain such as surgical resection and radiotherapy have been described. Surgical resection of brain stem lesions is challenging, and there are many surgical approaches described in literature. Endoscopic endonasal transsphenoidal transclival approach has not been widely used for anterior pontine metastasis.Herein, we present a case of 47 years old lady who was diagnosed with metastatic endometrial adenocarcinoma in the form of solitary pontine lesion after 3 years of initial diagnosis of uterine adenocarcinoma, which was operated via endoscopic endonasal transsphenoidal transclival approach followed by radiotherapy. Conclusion: Brain metastasis from endometrial cancer is rare, and its management depends on the number of lesions, the extent of disease and the general condition of the patient. Surgery followed by radiotherapy is a good option in isolated brain lesion with no evidence of extracranial lesion. Surgical resection of pontine lesions is challenging, and we suggest endoscopic endonasal transsphenoidal transclival approach for better exposure and resection.